DEVELOPMENT OF LAW IN THE PERSPECTIVE OF SOCIAL ORDER THROUGH PREEMTIF AND PREVENTIVE POLICY BASED ON LAW NO. 2 OF 2002 CONCERNING THE POLICE OF THE REPUBLIC OF INDONESIA - Surya Nita (NOMOI Law Review, 2022)
The development of law in Indonesia is marked by the development of society in social order which affects the legal system regarding awareness in applying the law through preemptive and preventive policies based on Law no. 2 of 2002 concerning the Indonesian National Police . That law enforcement is the duty and function of the Police that must be carried out in the Police. The meaning in the legal system consists of the formation of the rule of law, law enforcement by law enforcement officials, and legal awareness of the community in compliance and obedience as a legal community in maintaining social order. The research method used is normative juridical by analyzing the rule of law through the formation of law in Indonesia based on Law no. 15 of 2019 concerning Amendments to Law No. 12 of 2011 concerning the Establishment of Legislation; and Law no. 2 of 2002 concerning the Indonesian National Police .